The care of the witness : a contemporary history of testimony in crises / Michal Givoni. - Givoni, Michal (Human rights in history., 2016)
During the twentieth century, witnessing grew to be not just a widespread solution for coping with political atrocities but also an intricate problem. As the personal experience of victims, soldiers, and aid workers acquired unparalleled authority as a source of moral and political truth, the capacity to generate adequate testimonies based on this experience was repeatedly called into question. Michal Givoni's book follows the trail of the problems, torments, and crises that became commingled with witnessing to genocide, disaster, and war over the course of the twentieth century. By juxtaposing episodes of reflexive witnessing to the Great War, the Jewish Holocaust, and third world emergencies, The Care of the Witness explores the shifting roles and responsibilities of witnesses in history and the contribution that the troubles of witnessing made to the ethical consolidation of the witness as the leading figure of nongovernmental politics.